Pengaruh Pendidikan Kesehatan Berbasis Video terhadap Self Efficacy Anak Dalam Pencegahan Pelecehan Seksual di Sekolah Dasar - Habiba Sabrina Kunaifi; Rita Yulifah; Nurul Pujiastuti (HB PRESS, 2025)
Sexual abuse among children is a form of violence that often occurs but frequently remains undetected. Data from the Ministry of Women’s Empowerment and Child Protection show an increasing trend of child sexual abuse cases in Malang Regency from 2021 to 2024. Limited knowledge about sexuality and low self-efficacy make children more vulnerable because they may lack the confidence and skills to protect themselves in risky situations. Self-efficacy is important in preventing sexual abuse as it reflects a child’s confidence in responding to potential threats. Therefore, effective health education methods that engage children’s attention are needed, such as video-based learning. This study aimed to examine the effect of video-based health education on children’s self-efficacy in preventing sexual abuse. Using a pre-experimental one-group pretest–posttest design, 34 first- to third-grade students at State Elementary School Kalisongo 3 Malang participated. The results showed a significant increase in self-efficacy after the intervention (p = 0.000), indicating that video-based education effectively improves children’s ability and confidence to prevent sexual abuse.